40 years of shop floor resistance: Racial ordering and history of militant culture - Bhengu, Sithembiso (New Agenda: SA Journal of Social and Economic Policy, 2024)
Based on four decades of ethnographic research into growing workplace resistance and militancy in the 1980s and 1990s at a Durban rubber factory, SITHEMBISO BHENGU adds his own study of the factory workers – their struggles, identities and everyday lives – more than a decade into democracy. In piecing together their narratives over a span of four decades, he identifies the clear continuities in the objective conditions workers live and work in, as well as in their subjective consciousness, and also the significant discontinuities between the two critical eras of worker formations and struggle in South Africa.